2019
DOI: 10.1101/707687
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matching whole genomes to rare genetic disorders: Identification of potential causative variants using phenotype-weighted knowledge in the CAGI SickKids5 clinical genomes challenge

Abstract: Precise identification of causative variants from whole‐genome sequencing data, including both coding and noncoding variants, is challenging. The Critical Assessment of Genome Interpretation 5 SickKids clinical genome challenge provided an opportunity to assess our ability to extract such information. Participants in the challenge were required to match each of the 24 whole‐genome sequences to the correct phenotypic profile and to identify the disease class of each genome. These are all rare disease cases that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 71 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Group 4 (Pal, Kundu, Yin, & Moult, ) : The bioinformatics approach used by the group 4 resulted in five correct genome to patient matches: 17 (H), 56(N), 93(F), 95(C), and 99(B), and yielded candidate variants for each (Table , Table S3). Of note, ethnicity was stated for three of the five cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Group 4 (Pal, Kundu, Yin, & Moult, ) : The bioinformatics approach used by the group 4 resulted in five correct genome to patient matches: 17 (H), 56(N), 93(F), 95(C), and 99(B), and yielded candidate variants for each (Table , Table S3). Of note, ethnicity was stated for three of the five cases.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper has demonstrated that the use of specific HPO terms improves gene‐ranking with the top 10% of HPO terms being sufficient to rank the causative gene (Tomar, Sethi, & Lai, ). Unlike other submissions, SID#4 weighed the clinical terms by scoring the most serious and definitive (to a presumed disease) term in the profile with the highest value (Pal et al, & Moult, ). SID#8 built eight gene sets related to the diseases of interest and classified each case as belonging to one of those categories, rather than using all the genes associated with any of the HPO terms derived from the clinical descriptions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations